P64 Predicting the impact of tobacco price increase policies on copd burden in italy. (15th November 2017) - Jani, V; Potts, L; Pesce, G; Marcon, A; Accordini, S; Jarvis, D; Minelli, C
Abstract : Introduction and Objective: Smoking has a large health and economic burden on populations, much of which is through increased risk of COPD, a major cause of disease, disability and death. COPD is set to rise with population ageing, and smoking initiation rates are increasing in young adolescents across Europe. We used Health Impact Assessment (HIA) analysis to predict the potential impact of tobacco price increase policies, to which youngsters are particularly sensitive, on future COPD burden in Italy, a country with low tobacco price relative to the rest of Europe. Methods: As part of the Ageing Lungs in European Cohorts (ALEC) project (www.alecstudy.org ), we used DYNAMO-HIA for a Markov-based modelling approach to HIA analysis. Demographic and smoking data from the Italian population were used, together with data on the effects of smoking and health burden of COPD. A 'maximum' and a 'realistic' scenario were simulated to reflect different price increase policies: a 138% increase to match UK price (highest in Europe), and a 50% increase. Using published figures for price elasticities, we simulated changes to smoking behaviours over a 40 year period, evaluated their effects on COPD burden, and compared the two scenarios to a 'business as usual' scenario. Results: The projected population pyramid confirmed Italy as an ageing population with increasing COPD burden. Over the 40 year period, the maximum scenario showed reduction in smoking prevalence mainly through an increase in never smokers. Compared with 'business as usual', this translated in a substantial decrease in COPD incidence and prevalence, with consequent reduction in mortality and increase in average life expectancy. The realistic scenario showed effects of smaller magnitude in the same direction. Conclusions: Tobacco price increase policies would be effective in reducing future COPD burden in Italy. To provide a wider European perspective, we are now extending this work to countries with different smoking behaviours and tobacco prices.